Визначення поняття «толерантність» у працях британських учених - Мазуренко, Катерина (Studies in Comparative Education, 2015)
У статті розкрито зміст поняття толерантність через призму його розвитку, що не припиняється дотепер, описано та досліджено умови, за яких було сформовано це поняття і шляхи, якими воно поєднується з освітою загалом, зокрема релігійною освітою у школах Великої Британії. Також у статті йдеться про філософський та соціальний бік проблеми і політичний вплив на освіту та толерантність. <!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> В статье раскрыто значение понятия «толерантность» через историческую призму его развития, которое продолжается. Описаны и проанализированы условия, в которых было сформулировано это понятие и показана его взаимосвязь с религиозным образованием в школах Великобритании. Также в статье описаны философская и социальная стороны проблемы. <!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The article describes the sense of the notion “tolerance” in the historical usage and its development that is continuing today. Tolerance is defined as value and a social norm of civil society, manifested in the right of all individuals to be diverse in society, ensuring harmony between different faiths, political, ethnic and other social groups, respecting the great variety of world cultures, civilizations and peoples, preparedness to understanding and cooperation with people who differ in appearance, language and beliefs. The widespread phenomenon of non-confessional religious education in the late XX century contributed to understanding the goals, tasks, content and ways of organizing and implementing school religious education in the modern world. To adapt educational concepts and approaches to socio-cultural situation proved to be very important. The conditions under which the notion appeared and the ways it connected with the education are studied. The connection of the notion “tolerance” and the religious education in Great Britain is also presented. The article touches upon philosophical and social aspects of the problem. Among the most important factors of the process are: the secularization of society; technology development and information exchange related phenomenon of globalization, multiculturalism, commercialization of education and knowledge; systemic crisis of the cultural paradigm of modernism; the emergence of new global threats. The article grounds the importance of religious education and its positive influence on students’ tolerance formation. The political influence on the education and tolerance is also presented. The research concludes that religious aspect of education is important in both Europe and in Ukraine and the problem of tolerance needs further studying, especially in today's world. In pedagogics the problem of spirituality must be paid special attention to because it aims not only to develop, define, determine ways, means and methods of forming specific competencies, knowledge and skills, but also to instill and develop certain qualities, abilities, traits and behaviour. The importance of religious education studying as the essence of the educational process in today's educational science is emphasized. <!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> 1. Булгаков С. Свет невечерний / С. Булгаков. – М.: Республика, 1994, – С. 17–19. 2. Декларація принципів толерантності [Електронний ресурс] – Режим доступу: http;//school-sector.rlarn.ru/prava/zakony /<span style="font-size: 10.0pt;